Changing Metal Cycles and Human Health 1984
DOI: 10.1007/978-3-642-69314-4_7
|View full text |Cite
|
Sign up to set email alerts
|

The Contamination of Plants and Soils with Heavy Metals and the Transport of Metals in Terrestrial Food Chains

Abstract: Abstract. The most important sources of heavy metal contamination in their order of significance are air pollution, river sediments, sewage sludges, town waste composts, agricultural chemicals, and industrial waste.Lead accumulation in plants near highways and roads has decreased considerably since the law controlling the lead content of petrol came into force. Hazardous amounts of lead, however, are still concentrated 10-20 m along the sides of highways and roads, and in the strip of up to 5 m there are also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
110
8
5

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 205 publications
(138 citation statements)
references
References 18 publications
11
110
8
5
Order By: Relevance
“…The background value of Cu in plants (10 mg/kg) stated by Markert (1995) and Kula (1998) is only slightly higher than that stated by Markert (1995). The growth depression of sensitive plants was observed at 15-20 mg/kg Cu in tissues (Kloke et al 1984), and 10% yield decrease is most likely at Cu concentration within the range of 10-30 mg/kg (MacNicol and Beckett 1985). Cu concentrations in plants were mostly lower compared to the surface soil layers.…”
Section: Content Of Heavy Metals In Soils and Plantsmentioning
confidence: 73%
“…The background value of Cu in plants (10 mg/kg) stated by Markert (1995) and Kula (1998) is only slightly higher than that stated by Markert (1995). The growth depression of sensitive plants was observed at 15-20 mg/kg Cu in tissues (Kloke et al 1984), and 10% yield decrease is most likely at Cu concentration within the range of 10-30 mg/kg (MacNicol and Beckett 1985). Cu concentrations in plants were mostly lower compared to the surface soil layers.…”
Section: Content Of Heavy Metals In Soils and Plantsmentioning
confidence: 73%
“…The highest accumulation coefficient was for cadmium, then for nickel and the lowest for lead. According to Kloke et al (1984) and Kabata-Pendias and Pendias (1999) in the plant-soil system each metal has different absorption properties and, at the same time, different accumulation coefficient. According to those publications cadmium has the highest accumulation coefficient (1-10) while for nickel it is much lower (0.1-1), and for lead it was the lowest (0.01-0.1).…”
Section: Resultsmentioning
confidence: 99%
“…Among the crops, spinach had generally very high transfer factors, indicating that cultivation of this species, along with other leaf vegetables like Table 1. Relative accumulation of heavy metals in edible plant parts of different crops (Kloke et al 1984) Variation in heavy metal accumulation was also observed within the plant. Except for roots, the highest concentrations are found in leaves, whereas the lowest are typically observed in seeds (Machelett et al 1993).…”
Section: Selection Of Crops With Low Heavy Metal Uptakementioning
confidence: 95%
“…Genotypic differences in plant uptake of mineral elements are well documented (Kloke et al 1984). An overview on the general metal accumulation behaviour of the selected crop species is given in Table 1.…”
Section: Selection Of Crops With Low Heavy Metal Uptakementioning
confidence: 99%